Ten-year outcomes of surgical treatment of ischemic mitral regurgitation-a retrospective study - Vajpeyi, Anshuman; Panicker, Varghese T. (International Surgery Journal, 2023)
Background: Mitral regurgitation (MR) is a prevalent form of valvular heart disease, affecting millions of people worldwide. Primary MR occurs due to mitral valve dysfunction, while secondary MR is caused by left ventricle remodelling. The study aimed to investigate the long-term outcomes of patients with IMR after undergoing coronary surgeries, including coronary artery bypass graft (CABG) with or without mitral valve repair or replacement. Methods: Retrospective, observational study design was planned. Pre-operative and postoperative data were collected from 68 patients with ischemic MR who underwent coronary artery bypass surgery, with or without Mitral valve replacement or mitral valve repair. (That is CABG only/CABG+MVR/CABG+MVr) in the year between 2001 and 2010. Patients followed up at 3 months, 1 year, and 10 years after the procedure. Results: Significant improvements in New York heart association (NYHA) functional class and MR status were observed for all three surgical groups, namely, a) CABG surgery, b) coronary artery bypass graft surgery with mitral valve replacement (CABG+MVR), and c) coronary artery bypass graft surgery with mitral valve repair (CABG+MVr). After 10 years, redo surgery rates were minimal for CABG only and CABG+MVR groups of patients, while CABG+MVr required 20% redo surgery. Postoperative complications, such as left ventricle failure, were seen in the immediate postoperative period, leading to the death of those patients 3 months following the surgery. After 3 months, complications decreased over time for all groups. Conclusions: Surgical interventions effectively improved functional outcomes and reduced MR severity in patients with ischemic MR. Redo surgery rates were low for most patients, indicating the success of the initial procedures.